Association between operative technique and intrusive thoughts on health‐related Quality of Life 3 years after APE/ELAPE for rectal cancer: results from a national Swedish cohort with comparison with normative Swedish data. (17th April 2018) - Prytz, Mattias; Ledebo, Anna; Angenete, Eva; Bock, David; Haglind, Eva
Abstract: The aim of this prospective registry‐based population study was to investigate the association between QoL 3 years after surgery for rectal cancer and intrusive thoughts and to assess the association with the type of surgery (i.e., APE or ELAPE) in a population‐based national cohort. ELAPE has been proposed as a superior surgical technique for distal rectal cancer, but long‐term effects on QoL are not known. There are also no studies on the association of negative intrusive thoughts on patients′ self‐reported Quality of Life following surgery for distal rectal cancer. Negative intrusive thoughts are regarded as a marker of incomplete cognitive processing of the psychological trauma caused by, for example, a cancer diagnosis. Intrusive thoughts have been recognized as an important factor associated Quality of Life outcome following surgery for other malignancies. All Swedish patients operated with any kind of abdominoperineal resection in the years 2007–2009 were identified through the Swedish ColoRectal Cancer Registry (SCRCR)—the APER population. All patients alive 3 years after surgery and willing to participate were included. Data were collected from three different sources: the registry, the original operative notes, and a study‐specific questionnaire regarding health‐related QoL answered by the patients. Questions on QoL from a normative reference population were also collected for comparison. Fifty‐six percent of the APER population reported a low overall Quality of Life. There was no significant difference between the sexes. Among men, there was a difference in overall QoL, with a higher level in the normative population (48%) compared with the male APER population (39%). Overall QoL was compared to a normative Swedish population. Almost half of the patients experienced negative intrusive thoughts, which was associated with a lower overall Quality of Life. The frequency and severity of negative intrusive thoughts were significantly associated with a low overall QoL. There was no difference in overall QoL after standard, compared with extralevator abdominoperineal excision. A large proportion of survivors after abdominoperineal excision for rectal cancer has a Quality of Life compared with a normative population, but many suffer from negative intrusive thoughts, a symptom of stress, which significantly decrease overall Quality of Life. Abstract : Quality of Life following abdominoperineal excision for rectal cancer is affected by the presence of negative intrusive thoughts but can otherwise be compared with that of a healthy normative population. Results from a national Swedish cohort.